Cellular Compartmentalization, Glutathione Transport and Its Relevance in Some Pathologies - Héctor Vázquez-Meza; María Magdalena Vilchis-Landeros; Melissa Vázquez-Carrada; Daniel Uribe-Ramírez; Deyamira Matuz-Mares (MDPI AG, 2023)
Reduced glutathione (GSH) is the most abundant non-protein endogenous thiol. It is a ubiquitous molecule produced in most organs, but its synthesis is predominantly in the liver, the tissue in charge of storing and distributing it. GSH is involved in the detoxification of free radicals, peroxides and xenobiotics (drugs, pollutants, carcinogens, etc.), protects biological membranes from lipid peroxidation, and is an important regulator of cell homeostasis, since it participates in signaling redox, regulation of the synthesis and degradation of proteins (S-glutathionylation), signal transduction, various apoptotic processes, gene expression, cell proliferation, DNA and RNA synthesis, etc. GSH transport is a vital step in cellular homeostasis supported by the liver through providing extrahepatic organs (such as the kidney, lung, intestine, and brain, among others) with the said antioxidant. The wide range of functions within the cell in which glutathione is involved shows that glutathione's role in cellular homeostasis goes beyond being a simple antioxidant agent; therefore, the importance of this tripeptide needs to be reassessed from a broader metabolic perspective.